hw 03 solution

c 1 b2 hx l b s n m xa x n hx l

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: cosh HuL x1 - sinh HuL x1 Hd L using the notation x4 = Â c t = Â x and x m = Hx , y , z, x4L t x ' = cosh HuL x + Â sinh HuL x4 , y ' = y , z ' = z, x4 ' = cosh HuL x4 - Â sinh HuL x1 In matrix notation i j j j j mn 'm j x = Ln x or j j j j j j k x' y z z z y' z z= z z z z' z z z x4 ' { i cosh HuL j j j j 0 j j j j j 0 j j k -Â sinh HuL 0 1 0 0 1 HcL if b ª tanh HuL then g = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ...
View Full Document

This document was uploaded on 03/17/2014 for the course PHYSICS 600 at Purdue.

Ask a homework question - tutors are online